Using colour Gabor texture features for scene understanding - Setchell, C.J; Campbell, N.W (7th International Conference on Image Processing and its Applications, 1999)
Gabor (1946) filters have been used extensively as a model of texture for image interpretation tasks. This paper demonstrates that when a bank of Gabor filters is applied to an image, there are strong relationships between the outputs of the different filters. These relationships are used to devise a new texture feature which is capable of describing texture information in a concise manner. Information about the distributions of filter responses is also encoded in the new feature. Performance of the feature is assessed by applying it to an image region classification task and comparing results to those obtained using features which do not utilise the relationships between filter outputs. It is shown that the distribution information aids the classification task. The new feature performs comparably with the other features whilst yielding a significantly smaller feature vector. We then describe how the feature may be applied to colour images. It is shown that the inclusion of colour information is beneficial to the classification task and also that the choice of colour space is important. The classification results are then compared to those obtained using a 28 element feature encoding colour, position, shape, size, context and also texture. The new colour Gabor feature outperforms the more intuitive 28 element feature. We conclude by suggesting that the Gabor based feature may be capable of implicitly encoding some shape and context information.